2022-RA-894-ESGO Endometrioid ovarian carcinoma – real world evidence from a large transatlantic team initiative: First results of the LEOPARD study. (20th October 2022) - Grube, Marcel; Batchvarov, Dimtcho; Brummel, Koen; de Kroon, Cornelis D; Schochter, Fabienne; Heitz, Florian; Bartl, Thomas; Heublein, Sabine; Kulkarni, Anjali; Knoll, Katharina; Zeimet, Alain; Wimberger, Pauline; et al.
Abstract : Introduction/Background: According to the WHO2020 understanding endometrioid ovarian carcinoma (ENOC) is the second most frequent ovarian carcinoma histotype. However, most historical cohorts include a significant number of misclassified cases, possibly resulting in a rather clouded picture of this histotype. We aimed to establish a large cohort of validated ENOC allowing us to study cliniocopathological characteristics and evaluate therapeutic strategies applied on an international multicentre level. Methodology: After launching a transatlantic initiative, a cohort of 846 ENOC was assembled from 22 centers across Canada and Europe after central expert pathology review and immunohistochemical validation. A detailed chart review was performed by contributing centres including surgical and adjuvant therapy data. Results: At this time a complete data set is available from 595 patients. Median age at diagnosis was 55 years (28–94). 330(55.5%) patients were diagnosed with FIGO stage I, 160(26.9%) with stage II, 77(12.9%) with stage III and 16(2.7%) with stage IV disease. Grade distribution included 238(40.2%) G1, 240(40.6%) G2 and 112(19.0%) G3 tumors. In 193(32.4%) patients a diagnosis of synchronous endometrial carcinoma was made. Surgical lymph node staging was performed in 308(51.8%) cases. Positive nodes were revealed in 26/308(8.4%) cases, of which tumor spread beyond the pelvis was described in 20/26(76.9%) patients. All low-grade tumors were node-negative. Platinum-based chemotherapy was given in 60.2% stage I, 89.1% stage II, 91.8% stage III and 86.7% stage IV patients. 5-year disease specific survival was 95.7% in stage I, 87.2% in stage II, 56.6% in stage III and 15.8% in stage IV (p<0.0001). Conclusion: We were able to assemble a large multicentre ENOC cohort. The international LEOPARD team initiative stands to provide a solid picture of this unique histotype including a powerful statement on the value of lymph-node dissection and adjuvant chemotherapy. This type-specific approach will help to improve precision care for ENOC patients.